2010
DOI: 10.1029/2009gl041635
|View full text |Cite
|
Sign up to set email alerts
|

First basin‐wide experimental results on N2 fixation in the open Mediterranean Sea

Abstract: The Mediterranean Sea presents several biogeochemical anomalies compared to the global ocean. An unbalanced N budget, high nitrate/phosphate ratios in subsurface waters and low 15N/14N ratios in particulate and dissolved nitrogen suggest a significant occurrence of N2 fixation. This study presents, for the first time, a basin‐wide overview of direct measurements of N2 fixation, with values in the North Atlantic for comparison, during late spring 2007. Very low N2 fixation rates (0.052 ± 0.031 nmols N l−1d−1) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
69
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 32 publications
14
69
2
Order By: Relevance
“…In the eastern basin, N 2 fixation rates were low, especially at station C where they reached 0.4 ± 0.1 µmol m −2 d −1 , which is in agreement with recent data obtained by Ibello et al (2010) who also reported extremely low rates (0.5 to 2 µmol m −2 d −1 ) at three stations in the Levantine basin in May-June 2007. These low rates , , Webb et al, 2009).…”
Section: Eastern Mediterranean Sea (Stations B To C)supporting
confidence: 81%
See 2 more Smart Citations
“…In the eastern basin, N 2 fixation rates were low, especially at station C where they reached 0.4 ± 0.1 µmol m −2 d −1 , which is in agreement with recent data obtained by Ibello et al (2010) who also reported extremely low rates (0.5 to 2 µmol m −2 d −1 ) at three stations in the Levantine basin in May-June 2007. These low rates , , Webb et al, 2009).…”
Section: Eastern Mediterranean Sea (Stations B To C)supporting
confidence: 81%
“…However, molecular studies conducted over coastal stations in the eastern and western basin have clearly reported the presence of diazotrophic microorganisms related to Archaea, Proteobacteria and/or Cyanobacteria (Man-Aharonovich et al, 2007;Le Moal and Biegala, 2009), and of the diatom symbiont Richelia intracellularis (Bar Zeev et al, 2008). The potential of these organisms to bloom and fix dinitrogen at high rates in the P-depleted Mediterranean waters is still in debate; recent studies have indeed reported during the summer stratification period either high N 2 fixation rates at one isolated station in the Levantine basin (Rees et al, 2006), or extremely low rates at six stations distributed across the basin (Ibello et al, 2010). This leads to a difficulty in concluding about the biogeochemical importance of diazotrophy in this environment.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The nutrient budget for N and P has been used to explain why the EMS has an unusually high nitrate : phosphate ratio (28 : 1) in deep water and predict that there would be very limited N 2 fixation (Krom et al, 2004), which was subsequently confirmed by field measurements (Ibello et al, 2010;Yogev et al, 2011). Only two silica budgets have been attempted in the Mediterranean.…”
Section: Introductionmentioning
confidence: 99%
“…The processes that induce such atypical ratios are under debate, and two hypotheses have been proposed, involving either significant diazotrophic activity, or low denitrification rates in combination with external inputs of nutrients (Béthoux and Copin-Montégut, 1986;Krom et al, 2010). Direct N 2 fixation measurements conducted in the eastern and western Mediterranean basins have shown mainly low diazotrophic activity with punctual peaks at different sites or seasons (0.01-129 nmol N L −1 d −1 , Rees et al, 2006;Sandroni et al, 2007;Ibello et al, 2010). This heterogeneity in rates of N 2 -fixation implies the need of high frequency surveys to fully integrate, over the long term, the role of diazotrophy in Mediterranean biogeochemical cycles.…”
Section: Introductionmentioning
confidence: 99%